Temporal trends in acute kidney injury across health care settings in the Irish health system: a cohort study. (7th August 2018) - Stack, Austin G; Li, Xia; Kaballo, Mohammed A; Elsayed, Mohamed E; Johnson, Howard; Murray, Patrick T; Saran, Rajiv; Browne, Leonard D
Abstract: Background: Complete ascertainment of the true rates of acute kidney injury (AKI) and emerging trends are essential for planning of preventive strategies within health systems. Methods: We conducted a retrospective cohort study from 2005 to 2014 using data from regional laboratory information systems to determine incidence rates of AKI and severity Stages 1–3 in the Irish health system. Multivariable models were developed to explore annual trends and the contributions of demographic factors, clinical measures, geographic factors and location of medical supervision expressed as adjusted odds ratios (ORs) and 95% confidence intervals (CIs). Results: From 2005 to 2014, incidence rates of AKI increased from 6.1% (5.8–6.3) to 13.2% (12.7–13.8) per 100 patient-years in men and from 5.0% (4.8–5.2) to 11.5% (11.0–12.0) in women, P < 0.001. Stage 1 AKI accounted for the greatest growth in incidence, from 4.4% (95% CI 4.3–4.6) in 2005 to 10.1% (95% CI 9.8–10.5) in 2014 (P < 0.001 for trend). Compared with 2005, patients in 2014 were more likely to experience AKI [OR 4.53 (95% CI 4.02–5.1) for Stage 1, OR 5.22 (4.16–6.55) for Stage 2 and OR 4.11 (3.05–5.54) for Stage 3], adjusting for changing demographic and clinical profiles. Incidence rates of AKI increased in all locations of medical supervision during the period of observation, but were greatest for inpatient [OR 19.11 (95% CI 17.69–20.64)] and emergency room settings [OR 5.97 (95% CI 5.56–6.42)] compared with a general practice setting (referent). Conclusion: Incidence rates of AKI have increased substantially in the Irish health system, which were not accounted for by changing demographic patterns, clinical profiles or location of medical supervision.